PROSPEK ISLAM DALAM MENGHADAPI TANTANGAN ZAMAN - Azhar, Shopia (Universitas Islam Negeri Alauddin Makassar, 2017)
Geo-politics that can contribute to the role of Islam as a socio-cultural system is expected to increase from natural resources in countries that are predominantly Muslim, or officially call themselves Islamic countries. On the other hand there is still anxiety considering the backwardness of Muslims themselves, both in the field of science and technology, in addition to the blurring of Muslims in providing Islamic perceptions, or a kind of distortion of values that engulf the poverty that crippled the power of reason and creativity of Muslims; coupled with less obvious divisions, reasons and interests among Islamic leaders in some predominantly Islamic countries, which can assume the inability of Islamic leadership. One of the dilemmas facing Islamic society in the modernization process is how to place its religious values and orientation amidst rapidly changing changes in social life. On the one hand Muslims want to follow the motion of modernization and present themselves as a modern society, but on the other hand it still wants to not lose its personality traits that are marked by various values that have been embraced. In this kind of transition, there is often an attempt at orientation jumping, leaving behind a new, established value system, capable of being used as a necessary measure of insight and attitude, a personality distortion that brings about the stability of social life. It is important to seek the placement of religious values (Islam), in the process of modenisation and the process of social change with a more open, dialogical and contextual approach.